Is it time to eliminate federal corporate income taxes? - Edward Lane; Larry Randall Wray (Levy Economics Institute of Bard College, 2020)
Daycares closed on March 16, 2020 in Turkey to prevent the spread of COVID-19. At the same time, the two most common nonparental childcare arrangements in Turkey-care of children by grandparents and nannies-became undesirable due to health concerns and in some cases also unfeasible due to the partial lockdown for individuals under the age of 20 and over the age of 64. We estimate the potential impact of new constraints on nonparental childcare arrangements due to the pandemic on parental caregiving time of married parents of preschool-age children by using data from the 2014-15 Turkish Time Use Survey. Comparing how parental caregiving time varies by gender and use of nonparental childcare arrangements, we find that new constraints on nonparental childcare arrangements during the pandemic have potentially increased the gender difference in parental caregiving time by an hour and forty minutes in Turkey.
Keywords: B52; E12; E6; E62; G30; H20; H25; 330; Corporate Taxes; Tax Incidence; Modern Money Theory (MMT); Richard and Peggy Musgrave; Beardsley Ruml; Tax Reform